2018
DOI: 10.1093/tas/txy013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a partially de-oiled microalgae product in nursery pig diets1

Abstract: Although microalgae can be used as a source of energy and macronutrients in pig diets, there is limited information on the use of partially de-oiled microalgae coproducts in swine feeding programs. The objectives of this study were to evaluate the effects of a partially de-oiled microalgae extract (MAE) in nursery pig diets on growth performance and health status. A total of 300 pigs (initial BW = 6.3 ± 2.1 kg) were used in a 42-d experiment. Treatments included a standard corn-soybean meal control diet, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…They function as a rich source of food for the farming of finfish and crustaceans 9,179,180 . Currently, a study has revealed that the feeding of de‐oiled microalgae resulted in increased growth responses to nursery pigs 181 . A significant portion of global algal production (up to 30%) contributes to the feed industry 182 .…”
Section: Advanced Integrated Biorefinery Scheme To Produce Algae‐based Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…They function as a rich source of food for the farming of finfish and crustaceans 9,179,180 . Currently, a study has revealed that the feeding of de‐oiled microalgae resulted in increased growth responses to nursery pigs 181 . A significant portion of global algal production (up to 30%) contributes to the feed industry 182 .…”
Section: Advanced Integrated Biorefinery Scheme To Produce Algae‐based Productsmentioning
confidence: 99%
“…9,179,180 Currently, a study has revealed that the feeding of de-oiled microalgae resulted in increased growth responses to nursery pigs. 181 A significant portion of global algal production (up to 30%) contributes to the feed industry. 182 Arthrospira alone contributes about 50% of global production as a feed supplement 183 because of its tremendous dietary composition and high digestibility rate.…”
Section: Application Of Microalgae In the Animal Feed Industrymentioning
confidence: 99%
“…Current literature presents several results where the incorporation of small levels of microalgae increases animal performance, intestinal structure, and feed conversion, due to the promotion of beneficial bacteria in the gut, such as Lactobacillus [1]. Higher levels of incorporation, to supply major nutrients, have been reported with defatted microalgae biomass [11,12]. Ekmay et al [12] reported that the use of proteolytic enzymes improves the final weight of piglets fed with 10% Desmodesmus sp.…”
Section: Introductionmentioning
confidence: 99%